Pendampingan Membaca Al-Quran Dengan Metode Yanbu’a Untuk Meningkatkan Minat Anak Membaca Al-Qur’an Di TPQ Al-Amin Dusun Parerejo Gedangsewu Pare Kediri - Rohmad; M. Maimun Najjah; Muhammad Amrin syafi’i; Ishaq Purnomo (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2023)
This study aims to assess how the Yanbu'a method is applied to improve fluency in reading the Qur'an at TPQ Al-amin hamlet Parerejo Gedangsewu Pare Kediri. This study used a qualitative approach, using data collection techniques such as observation, interviews, and documentation. This objective involves fostering students who are obedient and highly moral, who excel in faith and intellectual, are able to adapt to contemporary situations, and are dedicated to mastering Diniyyah subjects. Inhibiting factors include that some students learn the Qur'an independently without adequate guidance from a knowledgeable scholar or teacher. In addition, there is a lack of awareness among students regarding the obligation to read the Qur'an for every Muslim.